1990
DOI: 10.1103/physrevlett.64.1654
|View full text |Cite
|
Sign up to set email alerts
|

Natural-parity states in superdeformed bands and pseudo SU(3) symmetry at extreme conditions

Abstract: The structure of recently discovered identical superdeformed bands in |S| Tb and ,52 Dy and in l50 Gd and 15, Tb are discussed in terms of the strong-coupling approach. Based on the experimental evidence that the superdeformed core of ,52 Dy is extremely insensitive to the polarization effects induced by the odd particle, the bands are shown to exhibit the presence of the pseudo SU(3) symmetry at extreme conditions of large elongations and high spins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
179
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(186 citation statements)
references
References 17 publications
6
179
1
Order By: Relevance
“…For example, (n r s 1/2 , (n r −1)d 3/2 ) will havel = 1, (n r p 3/2 , (n r −1)f 5/2 ) will havel = 2, etc. This pseudospin symmetry has been used to explain features of deformed nuclei [3], including superdeformation [4] and identical bands [5,6] and to establish an effective shell-model coupling scheme [7]. In view of its central role in both spherical and deformed nuclei, there has been an intense effort to understand the origin of this symmetry.…”
mentioning
confidence: 99%
“…For example, (n r s 1/2 , (n r −1)d 3/2 ) will havel = 1, (n r p 3/2 , (n r −1)f 5/2 ) will havel = 2, etc. This pseudospin symmetry has been used to explain features of deformed nuclei [3], including superdeformation [4] and identical bands [5,6] and to establish an effective shell-model coupling scheme [7]. In view of its central role in both spherical and deformed nuclei, there has been an intense effort to understand the origin of this symmetry.…”
mentioning
confidence: 99%
“…Similar to that of electrons orbiting in an atom, protons and neutrons in a nucleus generate shell structures, but different from the atomic systems, the corresponding nuclear magic numbers are found to be 2,8,20,28,50, and 82 for both protons and neutrons as well as 126 for neutrons in stable nuclei. In order to understand these magic numbers, simple models, such as the square-well or harmonic-oscillator (HO) potential, are not able to provide satisfactory answers.…”
Section: Introductionmentioning
confidence: 89%
“…Almost from then on, a number of phenomena in nuclear structure have been successfully interpreted directly or implicitly by the pseudospin symmetry, including nuclear superdeformed configurations [21,22,23,24,25], identical bands [26,27,28,29,30], quantized alignment [31], and pseudospin partner bands [32,33]. The pseudospin symmetry may also manifest itself in the magnetic moments and transitions [34,35,36] and γ-vibrational states in nuclei [37], as well as in nucleon-nucleus and nucleon-nucleon scatterings [38,39,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The notion of pseudospins= 1/2 was defined [17,18] to elucidate this quasidegeneracy in view of nonrelativistic quantum mechanics.s (pseudospin) andl (pseudo-orbital angular momentum) concepts were introduced to define a pseudospin doublet with total angular momentum j =s+l . Identical bands, magnetic moment, deformation, and superdeformation in nuclei were successfully expounded by considering the pseudospin concept [19][20][21][22][23][24][25]. In spite of knowing that the pseudospin initially was a nonrelativistic concept, its relativistic characteristic was discovered [26]; Ginocchio reported that usual l of the lower part of the Dirac spinor corresponds to the pseudo-orbital angular momentum.…”
Section: Introductionmentioning
confidence: 99%